Extended MHD simulations of infernal mode dynamics and coupling to tearing modes. (May 2015) - Brunetti, D; Graves, J P; Halpern, F D; Luciani, J-F; Lütjens, H; Cooper, W A
Abstract A numerical study of pressure driven magnetohydrodynamic (MHD) instabilities in a low-shear tight aspect ratio configuration is presented. When the magnetic shear is sufficiently small over an extended region in the core, enhanced instability occurs due to the coupling to poloidal sidebands, which itself occurs due to toroidicity. Numerical simulations have been performed with the initial value code XTOR-2F both in the ideal and resistive MHD frame. Two-fluid effects (plasma diamagnetic flows) have been retained as well. The predictions of the XTOR-2F code on the amplitude of the growth rate, and on the rotation frequency of the modes, have been compared with analytic linear theory of infernal modes. Qualitative agreement has been found between numerical and analytical results, in spite of the tight aspect ratio configuration. The intermediate scaling γ ∼ S−3/8, predicted by the linear theory (Brunetti et al 2014 Plasma Phys. Control. Fusion56 075025), is recovered by the numerical results. A study of the nonlinear evolution of the magnetic island of the tearing sideband has been performed and the results from the simulations are compared with Rutherford's theory.